Evaluation of the advantages of platelet concentrates stored at 4°C versus 22°C. Issue 3 (21st December 2017) - Yang, Jiangcun; Yin, Wen; Zhang, Yali; Sun, Yang; Ma, Ting; Gu, Shunli; Gao, Ying; Zhang, Xiaole; Yuan, Jun; Wang, Wenhua
Abstract : BACKGROUND: Platelet (PLT) storage at cold temperatures (4°C) can reduce bacterial contamination and lower the risk of transfusion‐related complications. We compared the effects of 22 and 4°C storage conditions for PLTs to further explore the efficiency of hemostasis in acute bleeding and extended PLT shelf life. STUDY DESIGN AND METHODS: Manually prepared PLTs (PLT concentrates in plasma, not PLT additive solution) were stored at 4 and 22°C. The PLT counts, scanning electronic microscope observations, blood gas indices, biochemical indices, PLT aggregative function, and surface CD62P expression were monitored and compared between the groups. RESULTS: There was no obvious change in PLT counts between Day 21 at 4°C and Day 5 at 22°C. PLTs stored at 4°C for 10 to 14 days were dramatically activated, had rough surfaces, and showed a significant degree of long pseudopodia formation. The pH of the PLTs on Day 5 was lower at 22°C than at 4°C, while the lactate dehydrogenase and lactic acid levels in the former group were significantly higher (p < 0.005). The maximum aggregation rates induced by collagen and arachidonic acid in the PLTs stored at 4°C for 5 days remained higher than 80%, while the rates induced by four inducers in the PLTs stored at 22°C were less than 5%. PLTs stored at 4°C for 10 to 14 days showed higher surface expression of PAC‐1 and CD62P. CONCLUSION: PLT counts, cellular morphologies, PLT membranes, cytoplasmic structures, aggregation rates, and hemostatic PLT function stored at 4°C for 10 to 14 days were better than those stored at 22°C for 5 days.